OXIDATION OF ARSENOPYRITE BY AIR AND AIR-SATURATED, DISTILLED WATER, AND IMPLICATIONS FOR MECHANISM OF OXIDATION - Nesbitt H.W.; Muir I.J.; Pratt A.R. (My University, 1995)
Arsenic and sulphur, and possibly iron, exist in multiple oxidation states in the near-surface of unoxidized arsenopyrite. X-ray photoelectron spectroscopy (XPS) of an unoxidized surface reveals that sulphur is present as disulphide (S2-2, 78 At. %), monosulphide (S2-, 15%), and as polysulphide (S2-n, where 2 < n < 8). As1- predominates, but 15% As0 is also observed. Most iron is present as Fe2+ bonded to arsenic and sulphur [Fe(II)-(As-S)], but some Fe3+ may be present, and bonded to As-S [Fe(III)-(As-S)].Exposure for twenty-five hours to the atmosphere reveals development of Fe(III)-oxyhydroxide species at the surface, with binding energies similar to goethite. Approximately one quarter of the arsenic is present as As5+, As3+, and As1+, although As1- predominates. Minor polysulphides and thiosulphate are produced during oxidation.Surfaces reacted with air-saturated, distilled water for eight hours undergo extensive oxidation. Fe(III)-oxyhydroxides are the dominant Fe surface species. As5+, As3+, and As1+ are as abundant as As1-, and sulphate is detectable on the surface. The binding energies and proportions of the oxygen-bearing species of the O(1s) spectra are effectively the same in the air-oxidized and water-reacted experiments. The striking similarities suggest strongly that the nature of the species produced, and their rates of formation, are the same during reaction with air and with air-saturated distilled water. The mechanisms by which oxygen near-surface species are produced may well be similar in both media.Arsenic is the most readily oxidized species, and sulphur is most slowly oxidized during reaction with the atmosphere. Reaction of arsenopyrite with air-saturated, distilled water oxidizes As1- and Fe2+ at similar rates, and much more rapidly than sulphur is oxidized.Auger depth profiles of oxidized arsenopyrite demonstrate that As diffuses from the interior of the mineral to the surface during oxidation. Diffusion of As to the oxidized surface, combined with the observed production of large amounts of As3+ and As5+ in the near-surface, combined with the observed arsenites and arsenates. Arsenites (ASO3-3) are particularly toxic to biota, and pose a potential risk to water quality where arsenopyrite is abundant.